Theoretical Foundations of the Use of Digital Technologies in the Professional Training of Future Teachers of Education - Dilfuza, Nasirova (International Journal of Formal Education, 2025)
The article substantiates the relevance of the task of modernizing the training and advanced training of teachers in the aspect of the formation of a digital culture. The purpose of the article is to reveal the author's concept of developing a professional educational program for the training of future teachers in the context of digitalization of education.